Techno Economic Analysis of Hybrid PLTD–PV-BESS Rental Pricing in West Kalimantan - Anggar Dewi Rwanita; Faiz Husnayain (International Journal of Electrical, Energy and Power System Engineering)
This study conducts a techno-economic and power quality analysis of a hybrid diesel generator–solar photovoltaic (PLTD–PLTS-BESS) power system in Ujung Said Village using HOMER and ETAP software. The HOMER simulation indicates that the 50% PLTD – 50% PLTS - BESS hybrid configuration offers the best balance between cost and technical performance, with the lowest Cost of Energy (COE) of IDR 4,067/kWh, a Net Present Cost (NPC) of IDR 83.7 billion, and a moderate initial investment of IDR 3.25 billion. This configuration also successfully reduces the Base Production Cost (BPP) of electricity from IDR 4,186/kWh to IDR 4,067/kWh. From the power quality perspective, harmonic analysis using ETAP shows that all configurations initially exceeded the IEEE 519-1992 standard limits for Total Harmonic Distortion current (THDi). However, after applying harmonic filters, the THDi of the 50% PLTD – 50% PLTS - BESS hybrid configuration decreased to 4.82%, meeting the required standard. The study also explores a leasing scheme for the PLTS component, which proves economically and technically feasible. Thus, the 50% PLTD – 50% PLTS – BESS hybrid configuration, supported by harmonic filtering and a leasing-based financing model, represents an optimal solution for efficient, reliable, and environmentally friendly rural electrification.